Assessment of the Effects of Compulsory Online Learning During Pandemic Time on Conceptual Knowledge Physics - Elmira Kushta, Dode Prenga, Silvana Miço, Polikron Dhoqina (Mathematical Statistician and Engineering Applications, 2022)
Herein we have considered a semi-analytic insight on effects of the online learning limitation during pandemic closure on the high school student’s knowledge in physics. The acknowledgment of the effects is realized by conducting standard concept inventory tests and analyzing their raw results and accompanying specifics features. The Rasch technique is used for assessment of question’s difficulties and student’s abilities to solve standard tests by which we identified the learning problems and drawbacks. After establishing frequent errors from the concept inventory test answers and evidencing the indecisiveness in responding questions, we used the Likert 5-scale instrument for a more detailed analysis. We concluded that the lack of demonstration and live laboratory work supporting physics teaching is the most influential factor for the temporal drawback observed.